Validation of the Toronto Psoriatic Arthritis Screen II (TOPAS II) questionnaire in a Turkish population - ŞANAL TOPRAK, CANAN; DURUÖZ, MEHMET TUNCAY (SPRINGER HEIDELBERG, 2018)
Objective To evaluate the TOPAS II questionnaire validation in a Turkish population. Methods The Turkish translation of ToPAS II was sent to us by the developer authors of the original index. Subjects were recruited from dermatology, physical medicine and rehabilitation, and rheumatology outpatient clinics. All patients' demographic parameters and ToPAS II questionnaire results were recorded. After patients completed the questionnaire they were assessed by a rheumatologist according to a standard protocol which includes a complete history, detailed physical examination, laboratory tests and CASPAR criteria. Receiver operating characteristics (ROC) assessed to obtain sensitivity and specificity of Turkish version of ToPAS II questionnaire. Results One hundred and fifty subjects were recruited in the study. The mean age of subjects was 41.07 years (SD 12.59) and the 58% of subjects were female. There were 46 subjects from psoriasis group, 43 subjects from psoriatic arthritis (PsA) group, 41 subjects from physical medicine and rehabilitation group and 20 subjects from rheumatology (non-PsA) group. The area under the ROC curve was 0.99 which means as excellent predictor and optimum cut-off threshold to discriminate patients diagnosed with PsA was 8 according to this ROC curve analysis. The overall sensitivity and specificity based on cut-off threshold of 8, were 95.8 and 98%, respectively. Conclusion The Turkish version of ToPAS II has high sensitivity and specificity. It is simple, not time consuming and useful tool to screen for PsA in both patients with and without psoriasis
Keywords: Psoriatic arthritis; Screening tools; Validation; Psoriasis; RISK-FACTORS; VERSION; TOOLS